ANALISIS PRINSIP-PRINSIP PENDIDIKAN DALAM PERSPEKTIF AL-QUR’AN (Studi Tafsir Surah At-Taubah Ayat 122) - Ikhtiari Sulam; Zulhaini Zulhaini; Helbi Akbar (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
Islamic education is physical and spiritual guidance carried out by educators to students so that they develop optimally towards the formation of the main personality in accordance with Islamic standards. Moreover, in the current era, it is an era full of competition and is expected to be a reference for the improvement of Islamic religious education teachers in the future. Over time, there are problems that accompany the educational process. One of the problems in the world of education is that there are still many Muslim communities who do not understand and implement the content and meaning of the verses of the Qur'an, the dichotomy of religious and general knowledge, work without the support of knowledge, expertise and skills possessed. The Qur'an as a book of instructions has given its directions to humans in all aspects of this life, including its instructions in terms of education. Therefore, this research was conducted to find out the principles of education in the perspective of the Qur'an contained in Surah At-Taubah verse 122 based on the study of the interpretation of the verse by using the tahlili interpretation method approach which was explained descriptively analytically and supported by data. data both primary and secondary. After conducting research, the authors found the principles offered by the Qur'an in education, namely: The principle of the obligation to study within the limits of fardhu kifayah, the Integral and Integrated Principle, the Principle of Practice and the Principle of Da'wah.